The hepatoprotective activity of Fenugreek seeds' extract against carbon tetrachloride induced liver toxicity in rats - Said A.M; Al-Khashali D.; Al-Khateeb E.; Al-Wakeel N (College of Pharmacy / Mustansiriyah University, 2011)
The liver subjected to a number of disorders caused by chemicals namely as hepatotoxicity. carbon tetrachloride (CCl4) the most wildly used in induction of liver injury as a hepatotoxic model for scientific researches. The role of plants in treatment and prevention of chemical-induced liver damage, was extensively studied. Accordingly, this study was designed to evaluate the hepatoprotective effect of the aqueous solution of the ethanolic extract of Fenugreek seeds (FGS) against CCl4 induced liver damage in rats. From analysis of results, the extract of FGS showed highly hepatoprotective effect against CCl4 induced-necrosis with less effect against fatty changes, this could be due to the antioxidant action of the active constituents in the extract that counteract and scavenge the intermediates free radicals of CCl4 that generating during lipid peroxidation, which is the main cause of necrotic damage, while limitations of these constituents to inhibit the intermediates involved during fatty changes which is unrelated to the oxidative stress. These results make the FGS as a good candidate to be used against drug induced hepatotoxicity.